Concrete bricks with recycled rubber fibers: an alternative material for social housing - Damiani Lazo, Carlos Arturo; Cáceres Larico, Set Moroni; Mamani Flores, Alex Gerardo (Ingeniería Solidaria, 2021)
Introduction: This research article “concrete brick with the addition of recycled rubber” was carried out in 2019 at the Faculty of Civil Engineering of the UNSA.Problem: The need to close the gap in the housing sector, especially for people with low economic resources and contribute to the reduction of atmospheric pollution due to the burning of tires in the manufacture of artisan bricks in the city of Arequipa.Objective: To find a more economical masonry unit with the same resistance as mechanized bricks, which can be manufactured and used by the inhabitants of the poorest segments of the city, using the rubber from used tires.Methodology: For the research we induce the object of study, through different additions of rubber in the mixture, this experimentation allows us to find through different tests, the physical and mechanical properties of the LCR, describing the results of the tests carried out on the LCR masonry units and KKH10.Originality:In the bibliographic review the use of recycled rubber is found in concrete, we propose to find a brick made with a mixture of concrete and recycled tire rubber fibers to replace the fine aggregate that we will call “Bricks with Recycled Rubber” (LCR), our purpose is that it achieves the same characteristics of a type IV unit and meets the minimum requirements established by Standard E.070Limitations:It has not been had since the materials used are of universal use, although it could be the quality of cement.Results: The LCR-I brick, which is classified as type IV, is of good quality, handcrafted, and friendly to the environment. This brick has a cost of $ 0.251 US dollars, that is, 12% cheaper than the most widely used mechanized brick in the city.
Keywords: rubber recycled; masonry; bricks; materials testing; social housing